2012
DOI: 10.1186/1749-8104-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin repellent signaling via ErbB4 restricts GABAergic interneurons to migratory paths from ganglionic eminence to cortical destinations

Abstract: BackgroundCortical GABAergic interneurons (INs) are generated in the medial ganglionic eminence (MGE) and migrate tangentially into cortex. Because most, if not all, migrating MGE-derived INs express the neuregulin (NRG) receptor, ErbB4, we investigated influences of Nrg1 isoforms and Nrg3 on IN migration through ventral telencephalon (vTel) and within cortex.ResultsDuring IN migration, NRG expression domains and distributions of ErbB4-expressing, MGE-derived INs are complementary with minimal overlap, both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 48 publications
4
54
0
Order By: Relevance
“…In one, Erbb4-expressing interneurons, in response to attractive, soluble Nrg1 Type I in the cortex, migrate on a permissive corridor of Nrg1 Type III through the developing striatum (Flames et al, 2004). In the other, Nrg1 and Nrg3 act as repellants that funnel interneurons as they migrate from the MGE to cortical destinations (Li et al, 2012a). Regardless, GABAergic interneurons are reduced in the cortex of Erbb4 mutant mice, which supports a role for Erbb4 in tangential migration (Fisahn et al, 2009; Flames et al, 2004; Li et al, 2012a; Schmucker et al, 2003).…”
Section: Assembly Of Neuronal Circuitrymentioning
confidence: 99%
See 2 more Smart Citations
“…In one, Erbb4-expressing interneurons, in response to attractive, soluble Nrg1 Type I in the cortex, migrate on a permissive corridor of Nrg1 Type III through the developing striatum (Flames et al, 2004). In the other, Nrg1 and Nrg3 act as repellants that funnel interneurons as they migrate from the MGE to cortical destinations (Li et al, 2012a). Regardless, GABAergic interneurons are reduced in the cortex of Erbb4 mutant mice, which supports a role for Erbb4 in tangential migration (Fisahn et al, 2009; Flames et al, 2004; Li et al, 2012a; Schmucker et al, 2003).…”
Section: Assembly Of Neuronal Circuitrymentioning
confidence: 99%
“…In the other, Nrg1 and Nrg3 act as repellants that funnel interneurons as they migrate from the MGE to cortical destinations (Li et al, 2012a). Regardless, GABAergic interneurons are reduced in the cortex of Erbb4 mutant mice, which supports a role for Erbb4 in tangential migration (Fisahn et al, 2009; Flames et al, 2004; Li et al, 2012a; Schmucker et al, 2003). It remains unclear, however, if genesis and/or survival of interneurons are altered in the mutant.…”
Section: Assembly Of Neuronal Circuitrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the long-term neurobehavioral effects of abolishing or diminishing levels of NRG3 in the brain have not been tested. In order to address this question, we generated a mouse model with a deletion of the Nrg3 gene and tested for neurobehavioral phenotypes [22]. We found that Nrg3 knockout (KO) mice displayed novelty-induced hyperactivity, impaired prepulse inhibition (PPI) of the acoustic startle response, and deficient fear conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…The NRG3 protein is a single-pass membrane protein with an extracellular N-terminal EGF-like domain that is cleaved to bind ErbB4 receptors [14,15,16], another schizophrenia susceptibility gene [17,18,19]. NRG3 and NRG1 are chemorepellant signals that guide GABAergic interneuron progenitors from their origin in the medial ganglionic eminence (MGE) through tangential migration to their final location in the developing cerebral cortex [20,21,22]. However, the long-term neurobehavioral effects of abolishing or diminishing levels of NRG3 in the brain have not been tested.…”
Section: Introductionmentioning
confidence: 99%